2019
DOI: 10.3390/ijerph16111957
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Assessment of the Toxic Heavy Metal Elements Abstracted from the Traditional Plant Cosmetics and Medical Remedies: Case Study of Libya

Abstract: Henna and walnut tree bark are widely used by Libyan women as cosmetics. They may contain lead (Pb), cadmium (Cd) and arsenic (As), which, in turn, pose a high risk to their health. This study aims to determine the levels of Pb, Cd and As in henna and walnut tree bark products sold in Libyan markets. The products were analyzed for their Pb, Cd and As content by using inductively coupled plasma mass spectrometry (ICP-MS) after a microwave acid digestion. The results showed a significant difference between the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The issue of hazard to health is sometimes being neglected or ignored. A study by Bobaker et al (2019) 27 indicated that such cosmetics might expose consumers to high levels of lead (Pb) and cadmium (Cd) and potentially led to health risk. This issue proves that the element of toyyib is not being fulfilled.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of hazard to health is sometimes being neglected or ignored. A study by Bobaker et al (2019) 27 indicated that such cosmetics might expose consumers to high levels of lead (Pb) and cadmium (Cd) and potentially led to health risk. This issue proves that the element of toyyib is not being fulfilled.…”
Section: Resultsmentioning
confidence: 99%
“…For Hg analysis, was utilized a dilute solution which contains 0.01 mol•L −1 of HNO 3 , 0.01 mol•L −1 of EDTA, and 10 μg•L −1 of Ga. All glassware was kept overnight in HNO 3 (10 % v/v) and rinsed several times with Millipore-Q water before its use to avoid cross-contamination. [3,20]. e present work utilized a digestion procedure using concentrated HNO 3 + HCl + H 2 O 2 for the determination of Pb, As, Cr, and Hg in six dietary supplements [2,24].…”
Section: Reagents and Standard Solutionsmentioning
confidence: 99%
“…However, the excellent analytical sensitivity that ICP-MS allows is indisputable. Table 3 shows other methods that had better LODs than those achieved in proposed TXRF methods [3,19]. Nevertheless, these methods utilized a larger amount of samples and reagents for digestion procedures in comparison with TXRF_DS_1 and TXRF_DS_2 methods.…”
Section: Figures Of Meritmentioning
confidence: 99%
See 2 more Smart Citations